Mechanical simulation and engineering utilization of limestone tailings in roadbed construction - Zheng, Chunyu; Li, Wenwei; Liu, Chenxu; Zheng, Wenhua; Cheng, Wei; You, Pengchao; Li, Xingjia (Frontiers in Built Environment, 2025)
This study investigates the engineering utilization of limestone tailings as subgrade filling material through comprehensive material characterization and mechanical simulation. Material properties were analyzed using laser particle size detection, XRD, and SEM, while mechanical behavior was assessed via direct shear and triaxial shear tests, revealing cohesion and internal friction angle values of 1.97 kPa and 30.67°, respectively, both complying with subgrade technical specifications. Integrating the case of the G207 Xiangyang reconstruction project, ABAQUS-based finite element simulations of conventional replacement scenarios showed a maximum settlement of 1.743 × 10−1 m at 5 m replacement depth under 25 kPa loading, which deviated by only 5.6% from field measurements and fully met highway standards. The validated computational framework establishes limestone tailings as a viable and sustainable alternative to natural soil, reducing resource consumption while maintaining structural integrity.